Proteomic characterisation of perhexiline treatment on THP-1 M1 macrophage differentiation - Dhakal, Bimala; Li, Celine Man Ying; Ramezanpour, Mahnaz; Houtak, Ghais; Li, Runhao; Bouras, George; Collela, Alex; Chegeni, Nusha; Chataway, Tim Kennion; Drew, Paul; Sallustio, Benedetta C.; Vreugde, Sarah; et al. (Frontiers in Immunology, 2023)
Background Dysregulated inflammation is important in the pathogenesis of many diseases including cancer, allergy, and autoimmunity. Macrophage activation and polarisation are commonly involved in the initiation, maintenance and resolution of inflammation. Perhexiline (PHX), an antianginal drug, has been suggested to modulate macrophage function, but the molecular effects of PHX on macrophages are unknown. In this study we investigated the effect of PHX treatment on macrophage activation and polarization and reveal the underlying proteomic changes induced. Methods We used an established protocol to differentiate human THP-1 monocytes into M1 or M2 macrophages involving three distinct, sequential stages (priming, rest, and differentiation). We examined the effect of PHX treatment at each stage on the polarization into either M1 or M2 macrophages using flow cytometry, quantitative polymerase chain reaction (qPCR) and enzyme linked immunosorbent assay (ELISA). Quantitative changes in the proteome were investigated using data independent acquisition mass spectrometry (DIA MS). Results PHX treatment promoted M1 macrophage polarization, including increased STAT1 and CCL2 expression and IL-1β secretion. This effect occurred when PHX was added at the differentiation stage of the M1 cultures. Proteomic profiling of PHX treated M1 cultures identified changes in metabolic (fatty acid metabolism, cholesterol homeostasis and oxidative phosphorylation) and immune signalling (Receptor Tyrosine Kinase, Rho GTPase and interferon) pathways. Conclusion This is the first study to report on the action of PHX on THP-1 macrophage polarization and the associated changes in the proteome of these cells.